Kimchi : essential recipes of the Korean kitchen - Byung-Hi, Lim; Byung-Soon, Lim; Kern, Anna; Francke, Henrik (London : Pavilion, 2014)
You can't really imagine Korea without kimchi. For thousands of years, their fermented vegetables have been absolutely essential at meals. In Korea, kimchi is so much more than food - it is a national cultural treasure, a universal health food and a part of the Korean identity.
Keywords: Kimchi- Cocina coreana